(untitled) (Revista INTEREDU11, 2021)
This article aims to analyze the challenges of implementing anti-racist public policies in education and ethnic-racial relations in Brazil based on Law No. 10.639 enacted in 2003 –mandatory teaching of African History in schools– and the Diretrizes Curriculares Nacionais para a Educação das Relações Étnico-raciais e para o Ensino de História e Cultura Afro-Brasileira e Africana, launched in 2005. We understand that the relationships between theories and concepts proposed by specialists in the field of anti-racist public policy and ethnic-racial education raise pertinent reflections around the fundamental concepts for this debate inserted in the educational field, above all, in the anti-racist struggles both in education and in Brazilian society. As a methodology, content analysis based on Bardin and used in order to carry out a qualitative analysis of the topic. As a result, we saw that Law No. 10.639/03 is having trouble to materialize the epistemic turn and, therefore, the effectiveness of the Law. However, there is good results generated by the stimuli in academic spheres with the advancement of research and the expansion of this theme in the area of education.